Fault Diagnosis of Wind Turbine Gearbox Under Nonstationary Condition based on Order Analysis - Dengli Zhao; Xiaoxu Chen; Hao Xu; Fangyi Li; Liming Wang; Yanyan Nie (Jixie chuandong)
Gearbox is the key transmission part of wind turbine. It bears complex non-stationary load for a long time，and is prone to crack，teeth broken，wear and other gear faults，resulting in safety accidents and economic losses. It is of great significance to diagnose the faults. In view of the problem that the traditional spectrum analysis method can't meet the fault diagnosis of the wind turbine gearbox under nonstationary condition，the order analysis method is used to study the fault diagnosis of the gearbox. The basic principle of the order analysis method is analyzed，and the characteristic order of the gearbox is deduced and summarized. Finally，the real wind field data is analyzed by the order analysis method，and the fault in gearbox is identified accurately.